Gender-Based Violence Against Trans* Individuals: A Netnography of Mary Gregory’s Experience in Powerlifting - Taha-Thomure, Raiya; Milne, Aalaya S.; Kavanagh, Emma J.; Stirling, Ashley E. (Frontiers in Psychology, 2022)
In the context of sport, a growing body of research has reported the prevalence of violence against athletes, including sexual, physical, and psychological violence and neglect, experienced by both women and men in sport. Preliminary research has reported that gender-diverse individuals, specifically transgender athletes, may have a greater vulnerability to experiences of violence in sport, but this remains an under-researched population. In addition to limited research specifically on violence experienced by transgender athletes in sport, there is also only emerging research on virtual violence against athletes, with previous research on virtual violence in sporting spaces highlighting how online spaces are sites that can foster widespread hostility and violence. This study builds on previous research by examining discourses of virtual violence faced by transgender powerlifter, Mary Gregory, following her expulsion from the 100% Raw Powerlifting Federation. This research used a netnographic approach—an online ethnographic case study design. Data were collected from online news sources, as well as social media platforms, including Instagram, Twitter, and YouTube and were analyzed using reflexive thematic analysis. The data provided an insight into the cyberculture of powerlifting, and the negotiation of space, or lack thereof, for Mary Gregory within this physical culture. Five themes of were generated, including invalidation of gender identity, dehumanization, infliction of derogatory and crude language, accusations of cheating, and being compared to cisgender athletes without nuance. The study highlights the presence of significant vitriol across virtual platforms directed at Mary Gregory and the underlying presence of negative gender-based violence again trans* (GBV-T*) discourse. This case provides examples of virtual gender-based violence and transphobia in sport, a lack of readiness to accept trans* athletes, and concerns for the safety of trans* athletes in sporting spaces.